KAJIAN DESKRIPSI SUMBER KEUANGAN DAERAH PASKA OTONOMI DAERAH - Okfitasari, Antin; Widiastuti, Arum (JURNAL ILMIAH EDUNOMIKA, 2024)
Regional autonomy has brought changes in regional government governance, including regional financial management. The aim of this research is to find out the sources of regional income after regional autonomy and to find out the problems that arise regarding regional sources of income from the perspective of the laws that regulate them. This research uses a descriptive qualitative approach with a literature review. This research data was collected from articles and statutory regulations that are relevant to the legal basis of regional finance before and after regional autonomy, sources of regional income and problems that arise related to regional income through Google, Google Scholar and ScienceDirect. Miles and Huberman's interactive model of data analysis is used as data analysis in this research. The research results show that there are changes in the categories and details of regional income from Law no. 17 of 2023, Law no. 32 of 2004 and Law no. 23 of 2014. There have been no changes in the Law. Regional balance certainly has the impact of inconsistencies in the categorization of central government transfer funds to regional governments. Keywords: Regional finance, regional autonomy, regional income, PAD, transfer funds